Effect of plant row spacing and herbicide use on weed aboveground biomass and corn grain yield - Acciares,H.A. (2006)
The use of narrow plant spacing in corn (Zea mays) has been suggested as a technological alternative to obtain grain yield increases, due to a better use of resources. The regular pattern could diminish intraspecific competition while favoring interspecific competition with weeds. The objective of this study was to analyze the effect of corn row spacing on weed aboveground biomass and corn grain yield. Field experiments were conducted during 2002/2003 and 2003/2004 growing seasons. Three corn hybrids with two-row width (0.70 and 0.35 m) were tested. A greater photosynthetic photon flux density (PPFD) interception with a lower weed aboveground dry matter in narrow row arrangement was obtained. Corn grain yield was greater in the narrow row arrangement than in the wide row spacing. This increase in grain yield was related to a better resource use that allows for a reduced interspecific competition. The use of reduced spatial arrangement appeared to be an interesting alternative to increase both the grain yield potential and corn suppressive ability against weeds in corn dryland production systems.